A Q-switched, mode-locked fiber laser using a graphene oxide-based polarization sensitive saturable absorber - Lee, J.; Koo, J.; Debnath, P.; Song, Y-W; Lee, J. H. (IOP PUBLISHING LTD, 2013)
We demonstrate the use of a graphene oxide (GO)-deposited D-shaped fiber as a polarization sensitive saturable absorber for the implementation of a stable Q-switched, mode-locked fiber laser. Using both features of nonlinear saturable absorption and large polarization dependence loss of GO-deposited D-shaped fiber, stable Q-switched mode-locked pulses are readily obtained from an erbium-doped fiber ring laser through simple intra-cavity polarization control under a fixed pump power. It is shown that bursts of sub-picosecond, mode-locked pulses with a Q-switching envelope of a similar to 2.63 mu s temporal width and a similar to 71.3 kHz repetition rate can readily be generated from the laser. It is also demonstrated that the operating regime of the pulsed laser can be readily changed between mode-locking, Q-switched mode-locking, and Q-switching simply by changing the polarization state of the oscillated beam within the cavity.
Keywords: EVANESCENT FIELD INTERACTION; CARBON NANOTUBE; LOCKING